Model Pembelajaran DisProBasLe Untuk Mata Kuliah Metodologi Penelitian di Fakultas FKIP Universitas Nahdlatul Ulama Lampung - Wahidah, Nina Ikhwati; Iskandar, Iskandar; Sakung, Nikki Tri; Susila, Heni Rita (Peneliti.net, 2024)
The Research Methodology course has an important role, providing an academic foundation for students to understand the basic principles of research. This course is key in preparing FKIP students to become leaders and innovators in the field of education. Several problems faced by students in this course: Students have difficulty finding relevant and interesting research topics, specific and clear research questions are often a challenge, difficulty designing appropriate research methods, the process of collecting data and analyzing data appropriately and compiling research reports which is systematic, coherent, and in accordance with the rules of scientific writing. Understand and apply the principles of research ethics, including the protection of research subjects and academic integrity. To overcome problems in this research methodology course, a learning model is needed that can achieve learning objectives effectively and efficiently. The aim of the research is to develop a learning model by combining two learning models, namely Discovery Learning and Problem Based Learning which is called the model (DisProBasLe). The research method used in this research is an adaptation of the ADDIE development model in combination with the Dick and Carey model for formative evaluation. The result of this research is a learning design learning model using the (DisProBasLe) model. This learning model is suitable for use in research methodology courses. This can be seen from feasibility tests from experts in their fields, one to one student tests, small groups of students who have used the learning model (DisProBasLe).